2017
DOI: 10.2196/mental.6022
|View full text |Cite
|
Sign up to set email alerts
|

Computerized Cognitive Behavioral Therapy to Treat Emotional Distress After Stroke: A Feasibility Randomized Controlled Trial

Abstract: BackgroundDepression and anxiety are common complications following stroke. Symptoms could be treatable with psychological therapy, but there is little research on its efficacy.ObjectivesThe aim of this study was to investigate (1) the acceptability and feasibility of computerized cognitive behavioral therapy (cCBT) to treat symptoms of depression and anxiety and (2) a trial design for comparing the efficacy of cCBT compared with an active comparator.MethodsOf the total 134 people screened for symptoms of depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 33 publications
0
33
0
1
Order By: Relevance
“…The results showed no clinically or statistically significant changes before treatment and immediately after treatment between treatment groups in all studies (Berger et al, 2017;Høifødt et al, 2013;Newby et al, 2013;Rollman et al, 2017;Simblett et al, 2017;Gilbody et al, 2017;de Graaf et al, 2009;Levin et al, 2011;de Graaf et al, 2011;Hickie et al, 2010;Kessler et al, 2009;Gilbody et al, 2015). Less than half of the patients recovered at post-treatment.…”
Section: Effects Of the Internet-based Interventionsmentioning
confidence: 87%
See 3 more Smart Citations
“…The results showed no clinically or statistically significant changes before treatment and immediately after treatment between treatment groups in all studies (Berger et al, 2017;Høifødt et al, 2013;Newby et al, 2013;Rollman et al, 2017;Simblett et al, 2017;Gilbody et al, 2017;de Graaf et al, 2009;Levin et al, 2011;de Graaf et al, 2011;Hickie et al, 2010;Kessler et al, 2009;Gilbody et al, 2015). Less than half of the patients recovered at post-treatment.…”
Section: Effects Of the Internet-based Interventionsmentioning
confidence: 87%
“…Even though the drop-out rate was related to improvement attributed to other concurrent treatments (Newby et al, 2013), a variety of adverse events was also reported during treatment. As a consequence of commencing iCBT, the patients experienced a negative impact on their general wellbeing and reported slightly worse mood and more anxiety (Salomonsson et al, 2017;Rollman et al, 2017;Simblett et al, 2017).…”
Section: Drop-out and Participants' Adherence To Icbt Throughout Selementioning
confidence: 99%
See 2 more Smart Citations
“…45 'Beating the blues' is a computerized cognitive behavioural therapy package to treat the post stroke depression symptoms with best evidence within primary care. 46…”
Section: Computerized Therapymentioning
confidence: 99%